Pengaruh Harga, Ulasan Produk, dan Sistem Pembayaran COD Terhadap Keputusan Pembelian di Shopee (Studi Kasus Mahasiswa FEB-ULB) - Umi Amalia Nasution; Elvina Harahap; Mulya Rafika (Journal of Business and Economics Research (JBE), 2022)
Phenomena that occur in Labuhanbatu University FEB students who make purchases on the Shopee application are regarding pricing, product reviews and payment procedures with cash on delivery (COD) transactions. This COD system is used by the Shopee application to increase consumer confidence in shopping online. This study aims to see the effect of price, product reviews, and COD payment systems on purchasing decisions at Shopee. The results of the joint hypothesis test (f test) show that price, product reviews, and COD payment systems have a significant effect on Purchase Decisions in the Shopee Application, where the value of Fcount (74.219) > Ftable (2.71) with a significant level of 0.000 < 0.1. So, it can be concluded that the better the price, product reviews, and COD payment system, the better the purchasing decisions made by FEB ULB students on the Shopee Application.